(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic had confirmed outbreaks in December 2019. Furthermore, according to the World Health Organization (WHO), the SARS-CoV-2 virus was declared a Public Health Emergency of International Importance. It is necessary to understand the impacts caused on the issues of the relationships of different social groups. Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by deficits that permeate communication and social interaction. Therefore, for this specific group, living with the pandemic can cause several problems. The present study aimed to highlight information about the impacts of the COVID-19 pandemic on children with ASD. This is an integrative literature review (RIL). The search for articles occurred in February 2021 in the PUBMED database and in the VHL library with descriptors: Child, COVID-19, Autism Spectrum Disorder. 89 articles were recovered and only 12 remained for full reading. The analysis of the selected studies showed positive and negative impacts on children with ASD during the pandemic. This whole context contributed mainly to the development of behavioral problems and increased anxiety and stress. In this sense, it is important for the family to implement a new routine and calmly deal with the situation.